Battery cell, method of manufacturing the same, battery device, and electric device

CN122930997APending Publication Date: 2026-10-16CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610062600.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-16
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但在实现对能量密度改善的同时,往往带来了循环稳定性的恶化,这成为本领域亟需解决的技术问题

Benefits of technology

[0046] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930997A_ABST
    Figure CN122930997A_ABST
Patent Text Reader

Abstract

The application discloses a battery monomer, a preparation method thereof, a battery device and a power utilization device. The battery monomer comprises an electrolyte and an electrode assembly. The electrode assembly comprises a positive electrode sheet, a negative electrode sheet and a separator arranged between the positive electrode sheet and the negative electrode sheet. The negative electrode sheet comprises a negative electrode current collector and a negative electrode film layer arranged on at least one side of the negative electrode current collector. The separator comprises a base film and a composite coating layer arranged on at least one side of the base film. The composite coating layer comprises inorganic particles and binder particles. The binder particles are embedded in the inorganic particles and form protrusions on the composite coating layer. The electrolyte comprises an additive. In a first direction, the size of the negative electrode film layer is H1, and H1 is greater than or equal to 160 mm. The first direction is parallel to the direction of gravity. The battery monomer has good volume energy density and cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, specifically to a battery cell and its preparation method, a battery device, and an electrical device. Background Technology

[0002] In recent years, battery cells have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, as well as in many fields such as power tools, electric bicycles, electric motorcycles, electric cars, military equipment, and aerospace.

[0003] As market demand for longer driving ranges of electrical devices increases, higher requirements are being placed on the energy density of individual battery cells. However, improving energy density often leads to a deterioration in cycle stability, which has become a pressing technical problem to be solved in this field. Summary of the Invention

[0004] This application aims to at least address one of the technical problems existing in the background art. Therefore, one object of this application is to provide a battery cell, a method for preparing the same, a battery device, and an electrical device, to improve the cycle performance of the battery cell.

[0005] A first aspect of this application provides a battery cell, an electrolyte, and an electrode assembly. The electrode assembly includes a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrode. The negative electrode includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The separator includes a base film and a composite coating disposed on at least one side of the base film. The composite coating includes inorganic particles and binder particles, with the binder particles embedded in the inorganic particles and forming protrusions on the composite coating. The electrolyte includes additives, including one or more of difluoroethylene carbonate, fluoroethylene carbonate, fluorocarboxylic acid ester, fluorobenzene, vinyl sulfate, vinyl sulfite, and propylene sulfite. The size of the negative electrode film layer is H1 along a first direction, where H1 is greater than or equal to 160 mm, and the first direction is parallel to the direction of gravity.

[0006] The energy density of a battery cell can be increased by increasing its size (e.g., the dimension H1 of the negative electrode film along the first direction is greater than or equal to 160 mm). However, the applicant found that increasing the energy density of a battery cell by increasing its size leads to a deterioration in cycle performance. With increased cell height, the distance between the two ends of a taller cell in the height direction is longer, resulting in insufficient top liquid absorption and retention capacity, leading to inadequate top wetting and poor electrolyte distribution uniformity in the height direction. This causes uneven electrolyte distribution in the negative electrode sheet along the cell height direction, resulting in top lithium plating, which in turn triggers internal short circuits and reduces cell lifespan. The applicant creatively discovered that using a separator with a composite coating combined with an electrolyte containing the aforementioned additives significantly improves the problem of top liquid deficiency in taller cells during the later stages of cycling, thus improving cell cycle life. Using only a composite coating including inorganic particles and binder particles can improve the liquid absorption capacity at the top of the cell; however, this mainly improves the climbing ability of organic solvents, and is unlikely to increase the lithium salt concentration of the electrolyte climbing to the top of the cell. The applicant discovered that the electrolyte containing the above-mentioned additives has a higher degree of matching between its surface tension and the surface energy of the separator with the composite coating, which reduces the contact angle and further improves the wettability of the electrolyte. This not only improves the liquid absorption capacity at the top of the battery cell, but also increases the concentration of lithium salt in the electrolyte at the top of the battery cell, thereby further improving the cycle life of the battery cell.

[0007] In some embodiments, the additive accounts for 1%-10% of the mass of the electrolyte.

[0008] In some embodiments, the additive accounts for 1.5%-8% of the mass of the electrolyte.

[0009] When the mass ratio of additives is within the above range, it is beneficial to improve the matching degree between the tension of the electrolyte and the surface energy of the separator with composite coating, thereby further improving the cycle life of the battery cell.

[0010] In some embodiments, the viscosity of the electrolyte is 1.2 mPa·s - 3.8 mPa·s at 25°C.

[0011] In some embodiments, the viscosity of the electrolyte is 2.49 mPa·s - 3.17 mPa·s at 25°C.

[0012] Having the electrolyte viscosity within the above range is beneficial for improving the matching degree between the electrolyte tension and the surface energy of the separator with the composite coating, thereby further improving the cycle life of the battery cell.

[0013] In some embodiments, the electrolyte further includes a lithium salt, wherein the lithium salt accounts for 6%-18% of the mass of the electrolyte.

[0014] In some embodiments, the electrolyte further includes a lithium salt, the concentration of which is 0.8 mol / L to 1.3 mol / L based on the volume of the electrolyte.

[0015] Within the above-mentioned range, lithium salt concentration can balance ionic conductivity and solvent stability, improve electrode wetting and ion migration rate, reduce the risk of liquid shortage and lithium plating at the top of the high-energy cell, thereby improving cycle life and ensuring high energy density release.

[0016] In some embodiments, the average particle size of the inorganic particles on the composite coating is 0.5 μm-3 μm.

[0017] Inorganic particles with particle sizes within the above range can maintain high dispersibility while fully utilizing capillary action.

[0018] In some embodiments, the average particle size of the binder particles on the composite coating is 5 μm-20 μm.

[0019] The average particle size of the binder particles is within the above range, which can prevent the agglomeration of small-sized inorganic particles, so that the inorganic particles are evenly distributed around the binder particles, significantly improving the capillary effect of the composite coating. On the other hand, it can play a suitable adhesive role, so that the positive electrode, the separator and the negative electrode can be stably attached, while ensuring that they do not shrink at high temperature and do not shed powder during cycling.

[0020] In some embodiments, based on the mass of the composite coating, the mass percentage of the binder particles is greater than or equal to 25%.

[0021] When the mass ratio of binder particles is within the above range, it can provide appropriate adhesion and good capillary action, improve the liquid absorption capacity of the separator, and thus further improve the cycle life of the battery cell.

[0022] In some embodiments, the average particle size ratio of the binder particles to the inorganic particles in the composite coating is (2-35):1.

[0023] The applicant creatively combines large-diameter binder particles with small-diameter inorganic particles as a composite coating on the separator, resulting in an average particle size ratio of (2-35):1 for the binder particles to inorganic particles in the composite coating. In this composite coating, the microtubular structure formed between the inorganic particles and the electrode surface exhibits capillary action, enhancing the separator's liquid absorption capacity. Furthermore, the binder particles prevent the aggregation of small-diameter inorganic particles, ensuring a uniform distribution of inorganic particles around the binder particles. This significantly improves the capillary effect of the coating, thereby enhancing the separator's liquid absorption capacity, alleviating the problem of liquid shortage at the top of high-energy-density cells, and achieving a balance between high energy density and high cycle life.

[0024] In some embodiments, the mass ratio of the binder particles to the inorganic particles is 1:(1-3).

[0025] When the mass ratio of binder particles to inorganic particles is within the above range, the composite coating provides appropriate adhesion while also providing good capillary action, improving the liquid absorption capacity of the separator, alleviating the problem of liquid shortage at the top of high-energy-density cells, and achieving a balance between high energy density and high cycle life.

[0026] In some embodiments, the thickness of the composite coating is 0.5 μm-10 μm.

[0027] With the thickness of the composite coating within the above range, the battery cell achieves both good cycle life and better volumetric energy density.

[0028] In some embodiments, the areal density of the composite coating is 2.4 g / m³. 2 -16.9g / m 2 .

[0029] With the areal density of the composite coating within the above range, the battery cell achieves both good cycle life and better volumetric energy density.

[0030] In some embodiments, the porosity of the isolation membrane is 30%-65%.

[0031] In this embodiment, the porosity of the separator within the above-mentioned range can improve the wetting rate and uniformity of the electrolyte while ensuring the mechanical strength of the separator, thereby further improving the cycle life of the high-performance battery cells.

[0032] In some embodiments, the binder particles include polyvinylidene fluoride copolymer, sodium carboxymethyl cellulose, polystyrene-butadiene copolymer, and hydrogenated styrene. Butadiene block copolymer, hydrogenated styrene Isoprene block copolymer, ethylene Butene copolymer, polypropylene Octene thermoplastic elastomer, ethylene Octene thermoplastic elastomers and propylene One or more of the ethylene copolymers.

[0033] In some embodiments, the inorganic particles include one or more of alumina (Al2O3), boehmite (AlOOH), silicon dioxide (SiO2), cerium oxide (CeO2), magnesium aluminate (MgAl2O4), zirconium oxide (ZrO), and titanium oxide (TiO2).

[0034] In some embodiments, the base film comprises one or more of polyolefins and polyamides.

[0035] In some embodiments, the thickness of the base film is 5 μm-10 μm.

[0036] In some embodiments, along the first direction, the size of the negative electrode film is H1, where H1 is 160mm-500mm. In some embodiments, the volumetric energy density of the battery cell is 412Wh / L-450Wh / L.

[0037] In the embodiments of this application, the above-mentioned volumetric energy density target is achieved while improving the cell's liquid absorption capacity.

[0038] An embodiment of the second aspect of this application provides a method for preparing a battery cell, comprising: forming an electrode assembly by forming a positive electrode sheet, a negative electrode sheet, and a separator, wherein the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector, the size of the negative electrode film layer being H1 along a first direction, H1 being greater than or equal to 160 mm, the first direction being parallel to the direction of gravity, the separator including a base film and a composite coating disposed on at least one side of the base film, wherein the composite coating includes inorganic particles and binder particles, the binder particles being embedded in the inorganic particles and forming protrusions on the composite coating; placing the electrode assembly in a housing, performing a first electrolyte injection, and allowing it to stand; performing a second electrolyte injection after standing, wherein the second electrolyte used for the second electrolyte injection includes an additive, the additive including one or more of difluoroethylene carbonate, fluoroethylene carbonate, fluorobenzene, ethylene sulfate, ethylene sulfite, and propylene sulfite, to obtain a battery cell.

[0039] In this application, an additive is added during the second electrolyte injection, which allows the additive to be retained in the electrolyte to a greater extent, adjusting the surface tension of the electrolyte and improving the matching degree between the electrolyte tension and the surface energy of the separator with the composite coating. This further improves the wettability of the electrolyte, and while improving the liquid absorption capacity at the top of the battery cell, it also increases the concentration of lithium salt in the electrolyte at the top of the battery cell, thereby further improving the cycle life of the battery cell.

[0040] In some embodiments, the additive accounts for 3.33%-66.67% of the mass of the second electrolyte.

[0041] In some embodiments, the additive accounts for 5%-53.33% of the mass based on the mass of the second electrolyte.

[0042] In some embodiments, the mass ratio of the first electrolyte to the second electrolyte used for the first injection is (70:30) to (85:15).

[0043] When the mass ratio of additives is within the above range, it is beneficial to improve the matching degree between the tension of the electrolyte and the surface energy of the separator with composite coating, thereby further improving the cycle life of the battery cell.

[0044] A third aspect of this application provides a battery device, comprising a battery cell as described in any of the embodiments of the first aspect above or a battery cell prepared in any of the embodiments of the second aspect above, wherein the battery device comprises one or more of a battery module and a battery pack.

[0045] A fourth aspect of this application provides an electrical device, the electrical device including a battery device as described in any of the third aspects above, the battery device being used to provide electrical energy.

[0046] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description

[0047] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the various drawings denote the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings depict only some embodiments disclosed in this application and should not be construed as limiting the scope of this application.

[0048] Figure 1 This is a schematic diagram of a battery cell according to one embodiment of this application; Figure 2 This is a scanning electron microscope image of the composite coating of a battery cell according to an embodiment of this application; Figure 3 yes Figure 2 A magnified view of a portion of region 1 in the middle; Figure 4 yes Figure 1 An exploded view of a battery cell according to one embodiment of this application is shown. Figure 5 This is a schematic diagram of a battery module according to one embodiment of this application; Figure 6 This is a schematic diagram of a battery pack according to one embodiment of this application; Figure 7 yes Figure 6 An exploded view of a battery pack according to one embodiment of this application is shown.

[0049] Explanation of reference numerals in the attached figures: 1 Battery pack; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Battery cell; 51 Housing; 52 Electrode assembly; 53 Cover plate assembly; 6 Adhesive particles; 7 Region 1; Z: First direction; X: Second direction; Y: Third direction. Detailed Implementation

[0050] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.

[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.

[0052] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.

[0053] In this document, the term "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. In the description of the embodiments of this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0054] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).

[0055] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.

[0056] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.

[0057] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0058] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0059] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0060] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0061] As market demand for longer driving ranges of electrical devices increases, higher requirements are being placed on the energy density of individual battery cells. However, improving energy density often leads to a deterioration in cycle stability, which has become a pressing technical problem to be solved in this field.

[0062] A first aspect of this application provides a battery cell including an electrolyte and an electrode assembly. The electrode assembly includes a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrode. The negative electrode includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The separator includes a base film and a composite coating disposed on at least one side of the base film. The composite coating includes inorganic particles and binder particles, with the binder particles embedded in the inorganic particles and forming protrusions on the composite coating. The electrolyte includes additives, including one or more of difluoroethylene carbonate, fluoroethylene carbonate, fluorocarboxylic acid ester, fluorobenzene, vinyl sulfate, vinyl sulfite, and propylene sulfite. The negative electrode film layer has a size H1 along a first direction, where H1 is greater than or equal to 160 mm, and the first direction is parallel to the direction of gravity.

[0063] Increasing the size of a battery cell (e.g., the dimension H1 of the negative electrode film along the first direction is greater than or equal to 160 mm) can improve the energy density of the battery cell. However, the applicant found that increasing the size of the battery cell to improve its energy density leads to poor cycle performance. With increased cell height, the distance between the two ends of a taller cell in the height direction is longer, resulting in insufficient top liquid absorption and retention capacity, leading to inadequate top wetting and poor electrolyte distribution uniformity in the height direction. This causes uneven electrolyte distribution in the negative electrode sheet along the cell height direction, resulting in top lithium plating, which in turn triggers internal short circuits and reduces cell lifespan. The applicant creatively discovered that using a separator with a composite coating combined with an electrolyte containing additives (non-solventized co-solvent) significantly improves the problem of top liquid deficiency in taller cells during the later stages of cycling, thus improving cell cycle life. Using only a composite coating including inorganic particles and binder particles can improve the top liquid absorption capacity of the battery cell; however, this mainly improves the climbing ability of the organic solvent, and is unlikely to improve the lithium salt concentration of the electrolyte climbing to the top of the cell. The applicant discovered that the electrolyte tension, including additives (non-solventized cosolvent), has a higher degree of matching with the surface energy of the separator with a composite coating, reducing the contact angle and further improving the wettability of the electrolyte. This not only improves the liquid absorption capacity at the top of the battery cell but also increases the concentration of lithium salt in the electrolyte at the top of the battery cell, thereby further improving the cycle life of the battery cell.

[0064] The first direction is parallel to the direction of gravity, where "direction of gravity" can refer to the direction of gravity of the battery cell when the electrical device is in use, or the direction of gravity of the battery cell when it is mounted on the electrical device. For example, when the vehicle is parked on a level surface, the direction of gravity of the battery cell is the height direction of the battery cell, and the first direction is parallel to the height direction of the battery cell. As an example, Figure 1 The Z-direction is the first direction, which is parallel to the direction of gravity and is also the height direction of the battery cell.

[0065] Figure 2 This is a scanning electron microscope (SEM) image of the composite coating of a battery cell according to an embodiment of this application. Figure 2 As shown, the binder particles are embedded in the inorganic particles and form protrusions on the composite coating.

[0066] In this document, the term "additive" refers to a non-solventizing cosolvent, which is a solvent component in the electrolyte that can coexist with lithium salts and solvents but does not form solvated coordination with lithium ions. For example, a non-solventizing cosolvent can coexist with carbonate solvents, ether solvents, or phosphate ester solvents in the electrolyte, but will not form a stable solvated complex with lithium ions. As examples, additives include one or more of difluoroethylene carbonate, fluoroethylene carbonate, fluorocarboxylic acid esters (such as ethyl trifluoroacetate (TFAE), tert-butyl trifluoroacetate, etc.), fluorobenzene, vinyl sulfate, vinyl sulfite, and propylene sulfite.

[0067] In this article, the types and mass contents of each component in the electrolyte can be obtained by any method known to those skilled in the art. As an example, gas chromatography can be used. Mass spectrometry (GC) MS, ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), gas chromatography Mass spectrometry (GC) One or more of the following (MS) are used to characterize the composition and content of the electrolyte. For example, refer to GB / T 9722 2023 "General Rules for Gas Chromatography of Chemical Reagents" and / or GB / T 6041 The 2020 "General Rules for Mass Spectrometry Analysis Methods" employs gas chromatography-mass spectrometry (GC / MS). After separating the components in the sample using GC, these components are further broken down into ion fragments in mass spectrometry, separated according to their mass-to-charge ratio (m / z) to form specific mass spectra. This allows for qualitative analysis of the organic components in the electrolyte. Subsequently, the organic components in the electrolyte are separated in a chromatographic column, generating detection signal spectra for each component. Component qualitative analysis is performed using retention time, and quantitative analysis is achieved by standardizing and correcting peak areas. This provides a quantitative analysis of the organic components in the electrolyte. (Refer to JY / T) 020. Ion chromatography is used to detect and quantify the types of anions in electrolyte salts in the electrolyte solution. Refer to JY / T 0578. In 2020, nuclear magnetic resonance spectroscopy (NMR) was used to obtain qualitative and quantitative analysis of the components in the electrolyte.

[0068] The electrolyte referred to in this article can be either fresh electrolyte (the sum of the first and second electrolyte fillers) or electrolyte obtained from disassembling a fully discharged battery cell. The electrolyte obtained from disassembling a fully discharged battery cell can be either the free electrolyte in the battery casing or the electrolyte obtained by centrifugation from the electrodes.

[0069] In this application, the fully discharged state refers to placing the battery cell at 25°C, letting it stand for 2 hours, maintaining the battery temperature at 25°C, discharging the battery at a constant current of 0.33C to 2.5V, letting it stand for 30 minutes, and then discharging it at a constant current of 0.04C to 2.5V.

[0070] In some embodiments, the additive accounts for 1%-10% of the mass of the electrolyte.

[0071] In some embodiments, the additive accounts for 1.5%-8% of the mass of the electrolyte.

[0072] In some embodiments, based on the mass of the electrolyte, the mass percentage of the additive is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any range between the two.

[0073] When the mass ratio of additives is within the above range, it is beneficial to improve the matching degree between the tension of the electrolyte and the surface energy of the separator with composite coating, thereby further improving the cycle life of the battery cell.

[0074] In some embodiments, the viscosity of the electrolyte is 1.2 mPa·s - 3.8 mPa·s at 25°C.

[0075] In some embodiments, the viscosity of the electrolyte is 2.49 mPa·s - 3.17 mPa·s at 25°C.

[0076] In some embodiments, the viscosity of the electrolyte at 25°C is 1.2 mPa·s, 1.3 mPa·s, 1.4 mPa·s, 1.5 mPa·s, 1.6 mPa·s, 1.7 mPa·s, 1.8 mPa·s, 1.9 mPa·s, 2.0 mPa·s, 2.1 mPa·s, 2.2 mPa·s, 2.3 mPa·s, 2.4 mPa·s, 2.5 mPa·s, 2.6 mPa·s, 2.7 mPa·s, 2.8 mPa·s, 2.9 mPa·s, 3.0 mPa·s, 3.1 mPa·s, 3.2 mPa·s, 3.3 mPa·s, 3.4 mPa·s, 3.5 mPa·s, 3.6 mPa·s, 3.7 mPa·s, or 3.8 mPa·s.

[0077] In this paper, the viscosity of the electrolyte can be detected by methods known in the art. As an example, at 25°C, a fully loaded battery cell is disassembled to obtain the electrolyte to be tested. The viscosity of the electrolyte can be measured using a digital rotational viscometer. Referring to GB / T10247-2008, the sample is placed in a constant temperature bath, the rotor is rotated at a set speed, the torque is measured and converted to obtain the viscosity value, and the average of three stable readings is taken as the test result.

[0078] In this application, the fully discharged state refers to placing the battery cell at 25°C, letting it stand for 2 hours, maintaining the battery temperature at 25°C, discharging the battery at a constant current of 0.33C to 2.5V, letting it stand for 30 minutes, and then discharging it at a constant current of 0.04C to 2.5V.

[0079] Having the electrolyte viscosity within the above range is beneficial for improving the matching degree between the electrolyte tension and the surface energy of the separator with the composite coating, thereby further improving the cycle life of the battery cell.

[0080] In some embodiments, the electrolyte further includes a lithium salt, wherein the lithium salt accounts for 6%-18% of the mass of the electrolyte.

[0081] In some embodiments, the electrolyte further includes lithium salt, and the mass percentage of the lithium salt, based on the mass of the electrolyte, is 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, or any range between the two.

[0082] In some embodiments, the electrolyte further includes a lithium salt, the concentration of which is 0.8 mol / L to 1.3 mol / L based on the volume of the electrolyte.

[0083] In some embodiments, the electrolyte further includes a lithium salt, and the concentration of the lithium salt is 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, or 1.3 mol / L, based on the volume of the electrolyte.

[0084] Within the above-mentioned range, lithium salt concentration can balance ionic conductivity and solvent stability, improve electrode wetting and ion migration rate, reduce the risk of liquid shortage and lithium plating at the top of the high-energy cell, thereby improving cycle life and ensuring high energy density release.

[0085] In some embodiments, the average particle size of the inorganic particles on the composite coating is 0.5 μm-3 μm.

[0086] In this paper, the "average particle size of the inorganic particles on the composite coating" can be detected by any method known in the art. As an example, a fully loaded battery cell is disassembled at 25°C, the separator is obtained, and placed under a scanning electron microscope (after observing the electrode edge under the scanning electron microscope, the field of view is adjusted to the center of the sample). Images are acquired using secondary electron mode, and electron microscope images are taken at 500x magnification. An EDS (Energy Dispersive Spectroscopy) spectrometer is used to perform area scanning of the scanning electron microscope images. The characteristic elements of the inorganic particles (such as Si, Mg, Zr, Ti, etc.) and the characteristic elements of the binder particles (such as F, etc.) are identified and distinguished. For example, based on the Si element distribution spectrum in the test area, particles clearly showing Si are inorganic particles, while particles not showing Si are binder particles. Figure 2 The binder particles 6 in the image. Due to the significant size difference between inorganic and organic particles, regions where a large number of characteristic elements of inorganic particles (such as Si, Mg, Zr, Ti, etc.) are clearly visible can be selected for further magnification to detect the particle size of the inorganic particles. For example, selecting... Figure 2 The middle region 1 was further magnified 10 times to obtain Figure 3 The particles in the electron microscope images were analyzed using ImageJ software (1.46r, Win64 version). The specific steps for using ImageJ are as follows: load the scanning electron microscope image to be analyzed; use the Cellpose plugin to identify the particles, and then manually correct or label them; finally, use ImageJ to read and analyze the statistical data. The "Feret" parameter of the particles obtained from the statistical analysis was used as the particle size. The average particle size of the inorganic particles was calculated by taking the particle size of 30-100 inorganic particles.

[0087] Understandably, inorganic particles are relatively rigid, and their particle size remains essentially unchanged before and after being used to prepare composite coatings.

[0088] In some embodiments, the average particle size of the inorganic particles on the composite coating is 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, or any value range between the two.

[0089] Inorganic particles with particle sizes within the above range can maintain high dispersibility while fully utilizing capillary action.

[0090] In some embodiments, the average particle size of the binder particles on the composite coating is 5 μm-20 μm.

[0091] In this paper, the "average particle size of the binder particles on the composite coating" can be detected by any method known in the art. As an example, a fully loaded battery cell is disassembled at 25°C, the separator is obtained, and placed under a scanning electron microscope (after observing the electrode edge under the scanning electron microscope, the field of view is adjusted to the center of the sample). Images are acquired using secondary electron mode, and electron microscope images are taken at 500x magnification. An EDS (Energy Dispersive Spectroscopy) spectrometer is used to perform area scanning of the scanning electron microscope images. The particles are identified and distinguished by recognizing the characteristic elements of inorganic particles (such as Si, Mg, Zr, Ti, etc.) and binder particles (such as F, etc.). For example, based on the Si element distribution spectrum in the test area, particles clearly showing Si are inorganic particles, while particles not showing Si are binder particles. Figure 2 The binder particles in the image were analyzed using ImageJ software (1.46r, Win64 version). The specific steps for using ImageJ are as follows: load the scanning electron microscope image to be analyzed; use the Cellpose plugin to identify the particles, and then manually correct or label them; finally, use ImageJ to read and analyze the data. The "Feret" parameter of the particles obtained from the statistical analysis was used as the particle size. The average particle size of the binder was calculated by taking the particle size of 30-100 binder particles.

[0092] Understandably, binder particles, being organic materials, are compressible. Their particle size changes after being used to prepare a composite coating; the average particle size before compression is 50%-90% of the average particle size after compression. As an example, using binder particles with an average particle size of 4 μm to prepare the first coating, and then preparing battery cells, disassembling the fully loaded battery cells to obtain the separator membrane, and observing the composite coating under a scanning electron microscope, the average particle size of the binder particles can be observed to be approximately 4.4 μm-8 μm.

[0093] In some embodiments, the average particle size of the binder particles on the composite coating is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, or any value range between the two.

[0094] The average particle size of the binder particles is within the above range, which can prevent the agglomeration of small-sized inorganic particles, so that the inorganic particles are evenly distributed around the binder particles, significantly improving the capillary effect of the composite coating. On the other hand, it can play a suitable adhesive role, so that the positive electrode, the separator and the negative electrode can be stably attached, while ensuring that they do not shrink at high temperature and do not shed powder during cycling.

[0095] In some embodiments, based on the mass of the composite coating, the mass percentage of the binder particles is greater than or equal to 25%.

[0096] In this paper, the "mass percentage of binder particles" can be determined using any method known in the art. As an example, a fully loaded battery cell was disassembled at 25°C, the separator was obtained, and the coating was scraped off and vacuum-dried at 60°C for 2 hours as the sample to be tested. This sample was then placed in a platinum crucible of a thermogravimetric analyzer. Under a nitrogen atmosphere, the temperature was increased to 800°C at a rate of 10°C / min, and the weight loss curve was recorded. Subsequently, the temperature was switched to air and held for 10-20 minutes until the mass stabilized. The final residual mass corresponds to the inorganic particle content, and the weight loss corresponds to the binder content.

[0097] In some embodiments, based on the mass of the composite coating, the mass percentage of the binder particles is 25%, 30%, 35%, 40%, 45%, 50%, or any value range between the two.

[0098] When the mass ratio of binder particles is within the above range, it can provide appropriate adhesion and good capillary action, improve the liquid absorption capacity of the separator, and thus further improve the cycle life of the battery cell.

[0099] In some embodiments, the average particle size ratio of the binder particles to the inorganic particles in the composite coating is (2-35):1.

[0100] In this paper, the average particle size of the binder particles and the inorganic particles on the composite coating can be obtained according to the above test method, and then the ratio between the two can be calculated.

[0101] In some embodiments, the average particle size ratio of the binder particles to the inorganic particles in the composite coating is 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1, 30:1, 31:1, 32:1, 33:1, 34:1, 35:1, or any range between the two.

[0102] The applicant creatively combines large-diameter binder particles with small-diameter inorganic particles as a composite coating on the separator, resulting in an average particle size ratio of (2-35):1 for the binder particles to inorganic particles in the composite coating. In this composite coating, the microtubular structure formed between the inorganic particles and the electrode surface exhibits capillary action, enhancing the separator's liquid absorption capacity. Furthermore, the binder particles prevent the aggregation of small-diameter inorganic particles, ensuring a uniform distribution of inorganic particles around the binder particles. This significantly improves the capillary effect of the coating, thereby enhancing the separator's liquid absorption capacity, alleviating the problem of liquid shortage at the top of high-energy-density cells, and achieving a balance between high energy density and high cycle life.

[0103] In some embodiments, the mass ratio of the binder particles to the inorganic particles is 1:(1-3).

[0104] In this paper, the mass content of binder particles and inorganic particles can be obtained according to the above test method, and then the mass ratio between the two can be calculated.

[0105] In some embodiments, the mass ratio of the binder particles to the inorganic particles is 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2.0, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3.0, or any range between the two.

[0106] When the mass ratio of binder particles to inorganic particles is within the above range, the composite coating provides appropriate adhesion while also providing good capillary action, improving the liquid absorption capacity of the separator, alleviating the problem of liquid shortage at the top of high-energy-density cells, and achieving a balance between high energy density and high cycle life.

[0107] In some embodiments, the thickness of the composite coating is 0.5 μm-10 μm.

[0108] In this paper, the thickness of the composite coating is defined in the context of the art and can be tested using methods known in the art. For example, a micrometer (e.g., a Mitutoyo 293-100 with an accuracy of 0.1 μm) can be used to test at least ten points, and the average value can be taken as the thickness of the composite coating. Alternatively, the separator can be cut with an ion beam, and then a scanning electron microscope can be used to observe the cross-section of the separator along the thickness direction to obtain the thickness of the composite coating.

[0109] In some embodiments, the thickness of the composite coating is 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, 8.0 μm, 8.5 μm, 9.0 μm, 9.5 μm, 10.0 μm, or any value range between the two.

[0110] With the thickness of the composite coating within the above range, the battery cell achieves both good cycle life and better volumetric energy density.

[0111] In some embodiments, the areal density of the composite coating is 2.4 g / m³. 2 -16.9g / m 2 .

[0112] In this paper, areal density has a known meaning in the art and can be tested using methods known in the art. For example, take a single-sided coated and hot-pressed release film (if it is a double-sided coated release film, the composite coating on one side can be scraped off first), punch it into a small circular piece with an area of ​​S1, weigh it, and record its weight as M1. Then wipe off the composite coating of the release film after weighing, weigh the base film, and record it as M0. The areal density of the composite coating = (M1-M0) / S1. To ensure the accuracy of the test results, multiple groups (e.g., 10 groups) of samples can be tested, and the average value can be calculated as the test result, with the unit being g / m³. 2 .

[0113] In some embodiments, the areal density of the composite coating is 2.4 g / m³. 2 3 g / m 2 4 g / m 2 5 g / m 2 6g / m 2 7 g / m 2 8 g / m 2 9 g / m 2 10 g / m 2 11 g / m 2 12 g / m 2 13 g / m 2 14 g / m 2 15 g / m 2 16 g / m 2 16.9 g / m 2 , or a range of values ​​between any two.

[0114] With the areal density of the composite coating within the above range, the battery cell achieves both good cycle life and better volumetric energy density.

[0115] In some embodiments, the porosity of the isolation membrane is 30%-65%.

[0116] In this article, porosity refers to the percentage of the volume of the separator's internal pores relative to its total volume. Porosity can be tested according to the standard GB / T 36363-2018 "Polyolefin Separators for Battery Cells". It should be noted that the actual testing process may differ slightly from the standard due to differences in testing instruments, testing errors, and to minimize the impact on porosity testing, in order to obtain more accurate test values.

[0117] In some embodiments, the porosity of the isolation membrane is 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, or any range between the two.

[0118] In this embodiment, the porosity of the separator within the above-mentioned range can improve the wetting rate and uniformity of the electrolyte while ensuring the mechanical strength of the separator, thereby further improving the cycle life of the high-performance battery cells.

[0119] In some embodiments, the binder particles include polyvinylidene fluoride copolymer, sodium carboxymethyl cellulose, polystyrene-butadiene copolymer, and hydrogenated styrene. Butadiene block copolymer, hydrogenated styrene Isoprene block copolymer, ethylene Butene copolymer, polypropylene Octene thermoplastic elastomer, ethylene Octene thermoplastic elastomers and propylene One or more of the ethylene copolymers.

[0120] In some embodiments, the inorganic particles include one or more of alumina (Al2O3), boehmite (AlOOH), silicon dioxide (SiO2), cerium oxide (CeO2), magnesium aluminate (MgAl2O4), zirconium oxide (ZrO), and titanium oxide (TiO2).

[0121] In some embodiments, the base film comprises one or more of polyolefins and polyamides.

[0122] In some embodiments, the thickness of the base film is 5 μm-10 μm.

[0123] In some embodiments, the thickness of the base film is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any value range between the two.

[0124] In some embodiments, along the first direction, the size of the negative electrode film is H1, where H1 is 160mm-500mm. In some embodiments, along the first direction, the size of the negative electrode film layer is H1, where H1 is 160mm, 170mm, 180mm, 190mm, 200mm, 210mm, 220mm, 230mm, 240mm, 250mm, 260mm, 270mm, 280mm, 290mm, 300mm, 310mm, 320mm, 330mm, 340mm, 350mm, 360mm, 370mm, 380mm, 390mm, 400mm, 410mm, 420mm, 430mm, 440mm, 450mm, 460mm, 470mm, 480mm, 490mm, 500mm, or any value range between the two.

[0125] In some embodiments, the volumetric energy density of the battery cell is 412Wh / L-450Wh / L.

[0126] In this paper, volumetric energy density can be measured using methods and equipment known in the art. As an example, a battery cell is left to stand at 25°C for 2 hours. Then, at 25°C, the cell is charged at 0.33C (0.33% of its nominal capacity) to the charging cutoff voltage of 3.65 V, left to stand for 10 minutes, and then charged at a constant voltage of 3.65 V until the current reaches 0.05C, at which point charging is stopped. The battery cell is then left to stand at 25°C for 1 hour, and then discharged at 0.33C to the discharge cutoff voltage of 2.5 V at 25°C. The total discharge energy of the battery cell is recorded as E0 (Wh). The volume of the battery cell is measured as V0 (L). The volumetric energy density of the battery cell = discharge energy of the battery cell E0 / volume of the battery cell V0, in Wh / L.

[0127] In some embodiments, the volumetric energy density of the battery cell is 412 Wh / L, 413 Wh / L, 414 Wh / L, 415 Wh / L, 416 Wh / L, 417 Wh / L, 418 Wh / L, 419 Wh / L, 420 Wh / L, 421 Wh / L, or 422 Wh / L. Wh / L, 423Wh / L, 424Wh / L, 425Wh / L, 426Wh / L, 427Wh / L, 428Wh / L, 429Wh / L, 430Wh / L, 431Wh / L, 432Wh / L, 433Wh / L, 434Wh / L, 435Wh / L, 436Wh / L, 437Wh / L, 438Wh / L, 439Wh / L, 440Wh / L, 441Wh / L, 442Wh / L, 443Wh / L, 444Wh / L, 445Wh / L, 446Wh / L, 447Wh / L, 448Wh / L, 449Wh / L, 450Wh / L, or any range of values ​​between the two.

[0128] In the embodiments of this application, the above-mentioned volumetric energy density target is achieved while improving the cell's liquid absorption capacity.

[0129] An embodiment of the second aspect of this application provides a method for preparing a battery cell, comprising: forming an electrode assembly by forming a positive electrode sheet, a negative electrode sheet, and a separator, wherein the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector, the size of the negative electrode film layer being H1 along a first direction, H1 being greater than or equal to 160 mm, the first direction being parallel to the direction of gravity, the separator including a base film and a composite coating disposed on at least one side of the base film, wherein the composite coating includes inorganic particles and binder particles, the binder particles being embedded in the inorganic particles and forming protrusions on the composite coating; placing the electrode assembly in a housing, performing a first electrolyte injection, and allowing it to stand; performing a second electrolyte injection after standing, wherein the second electrolyte used for the second electrolyte injection includes an additive, the additive including one or more of difluoroethylene carbonate, fluoroethylene carbonate, fluorobenzene, ethylene sulfate, ethylene sulfite, and propylene sulfite, to obtain a battery cell.

[0130] In this application, an additive is added during the second electrolyte injection, which allows the additive to be retained in the electrolyte to a greater extent, adjusting the surface tension of the electrolyte and improving the matching degree between the electrolyte tension and the surface energy of the separator with the composite coating. This further improves the wettability of the electrolyte, and while improving the liquid absorption capacity at the top of the battery cell, it also increases the concentration of lithium salt in the electrolyte at the top of the battery cell, thereby further improving the cycle life of the battery cell.

[0131] In this article, it can be understood that the outer casing can be the casing of a soft-pack battery, such as an aluminum-plastic film, or the casing of a hard-shell battery, such as an aluminum casing or a stainless steel casing.

[0132] In some embodiments, the additive accounts for 3.33%-66.67% of the mass of the second electrolyte.

[0133] In some embodiments, the additive accounts for 5%-53.33% of the mass based on the mass of the second electrolyte.

[0134] In some embodiments, based on the mass of the second electrolyte, the mass percentage of the additive is 3.33%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 66.67%, or any range between the two.

[0135] In some embodiments, the mass ratio of the first electrolyte to the second electrolyte used for the first injection is (70:30) to (85:15).

[0136] In some embodiments, the mass ratio of the first electrolyte to the second electrolyte used for the first injection is 70:30, 72:28, 74:26, 75:25, 76:24, 77:23, 78:22, 79:21, 80:20, 81:19, 82:18, 83:17, 84:16, 85:15, or any range between the two.

[0137] When the mass ratio of additives is within the above range, it is beneficial to improve the matching degree between the tension of the electrolyte and the surface energy of the separator with composite coating, thereby further improving the cycle life of the battery cell.

[0138] A third aspect of this application provides a battery device, comprising a battery cell as described in any of the embodiments of the first aspect above or a battery cell prepared in any of the embodiments of the second aspect above, wherein the battery device includes one or more of a battery module and a battery pack.

[0139] A fourth aspect of this application provides an electrical device, the electrical device including a battery device as described in any of the third aspects above, the battery device being used to provide electrical energy.

[0140] Typically, a battery cell includes a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.

[0141] [Positive electrode plate] The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, the positive electrode film layer including the positive electrode active material of the first aspect of this application.

[0142] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0143] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0144] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0145] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0146] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0147] [Negative electrode plate] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0148] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0149] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0150] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0151] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0152] [Electrolytes] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.

[0153] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0154] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0155] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0156] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.

[0157] [Battery cell] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding process.

[0158] In some embodiments, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.

[0159] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a flexible package, such as a pouch. The material of the flexible package can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0160] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 The example shown is a square-structured battery cell 5.

[0161] In some implementations, refer to Figure 4 The outer packaging may include a housing 51 and a cover assembly 53. The housing 51 and the cover assembly 53 enclose a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover assembly 53 can cover the opening to close the receiving cavity. A positive electrode, a negative electrode, and a separator can be formed into an electrode assembly 52 through a winding or stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in a single battery cell 5 can be one or more, which can be selected by those skilled in the art according to specific practical needs.

[0162] [Battery Device] This application also provides a battery device, which includes the battery cell provided in this application. In some embodiments, the battery device is one or more of a battery module and a battery pack.

[0163] In some implementations, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.

[0164] Figure 5 This is battery module 4, used as an example. (See reference...) Figure 5 In battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.

[0165] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0166] As an example, a battery pack may include a battery box and multiple battery modules disposed within the battery box. The battery box includes an upper body and a lower body, the upper body covering the lower body to form a closed space for accommodating the battery modules. The multiple battery modules can be arranged in any manner within the battery box.

[0167] Figure 6 and Figure 7 This is battery pack 1 as an example. (See reference...) Figure 6 and Figure 7 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0168] [Electrical appliances] In addition, this application also provides an electrical device, which includes at least one of the battery cell, battery module, or battery pack provided in this application. The battery cell, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device.

[0169] As the electrical device, a single battery cell, a battery module, or a battery pack can be selected according to its usage requirements.

[0170] The electrical devices include electric trucks, electric buses, electric ships, electric medium and large-sized vans, and construction machinery. To meet the requirements of these devices for long cycle life and high energy density of individual battery cells, battery packs or battery modules can be used.

[0171] To meet the requirements of this electrical device for long cycle life and high energy density of individual battery cells, battery packs or battery modules can be used.

[0172] I. Implementation Examples The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0173] Example 1 1) Preparation of positive electrode sheet The positive electrode active material (lithium iron phosphate), conductive agent (Super-P), and binder (polyvinylidene fluoride) are uniformly mixed in a weight ratio of 98:0.5:1.5, and a solvent (N-methylpyrrolidone, NMP) is added. The mixture is then coated on both sides of an aluminum foil, and after cold pressing and cutting, a positive electrode sheet is obtained.

[0174] 2) Preparation of negative electrode sheet The negative electrode active material (graphite), conductive agent (Super-P), binder (styrene-butadiene rubber), and dispersant (carboxymethyl cellulose) are uniformly mixed in a weight ratio of 97.9:0.7:0.5:0.9. Solvent (deionized water) is added, and the mixture is coated on both sides of copper foil. After cold pressing and cutting, the negative electrode sheet is obtained.

[0175] 3) Separating membrane Using 5 μm polyethylene (PE) as the base film, alumina (average particle size 2 μm) and polyvinylidene fluoride (average particle size 0.5 μm) were added to a solvent (NMP) at a mass ratio of 2:1 and mixed thoroughly. The final product was 8.5 g / m³ of solids. 2 The single-sided coating density is applied to both sides of the base film to form a composite coating (first coating), thus obtaining the isolation film.

[0176] The thickness of the single-sided composite coating is 2.5 μm, the top of the separator extends 10 mm beyond the negative electrode film, and the porosity of the separator is 35%.

[0177] 4) Preparation of electrolyte One electrolyte: In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), lithium salt (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (volume ratio 4:6), and stirred until homogeneous to obtain an electrolyte with a lithium salt concentration of 1.1 mol / L (0.9 mol / L LiPF6, 0.2 mol / L LiFSI).

[0178] Second electrolyte preparation: In an argon-atmospheric glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), lithium salt (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in the organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (volume ratio 4:6), stirred until homogeneous, and then 25% (by mass) of fluorobenzene was added to obtain an electrolyte with a lithium salt concentration of 1.1 mol / L (0.9 mol / L LiPF6, 0.2 mol / L LiFSI).

[0179] 5) Preparation of battery cells The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The cells are then wound to form the battery cell. Tabs are welded onto the cell, and the cell is installed in an aluminum casing. A first injection of electrolyte is then injected and the cell is allowed to stand for 12 hours. A second injection of electrolyte is then injected and the casing is sealed. After processes including standing, cold pressing, formation, shaping, and capacity testing, a lithium-ion secondary battery is obtained. The mass ratio of the first to second injections of electrolyte is 80:20.

[0180] The positive electrode film has a size of 248 mm, the negative electrode film has a size of 252 mm, the cell mass margin is 89.3%, and the electrolyte ionic conductivity was measured to be 11 mS / cm after disassembling the battery.

[0181] Examples 2-5 The preparation methods of the battery cells in Examples 2-5 are similar to those in Example 1, except that the particle sizes of the inorganic particles and binder particles used are different. The particle sizes and average particle sizes of the binder particles and inorganic particles on the composite coatings prepared in Examples 2-5 are shown in Table 1 below.

[0182] Examples 6-11 The preparation methods of the battery cells in Examples 6-11 are similar to those in Example 3, except that the amount of fluorobenzene added to the electrolyte is different, as detailed in Table 3 below.

[0183] Examples 12-13 The preparation methods of the battery cells in Examples 12-13 are similar to those in Example 3, except that the height of the negative electrode film is different, as shown in Table 4 below.

[0184] Comparative Example 1 The preparation method of the battery cell in Comparative Example 1 is similar to that in Example 3, except that no fluorobenzene is added to the electrolyte and the coating of the separator is a double-layer coating.

[0185] Preparation of the separator in Comparative Example 1: To prepare the first slurry, alumina (average particle size 1 μm) and polyvinylidene fluoride (average particle size 4 μm) were added to a solvent (NMP) at a mass ratio of 95:5 and mixed evenly. To prepare the second slurry, polyvinylidene fluoride (average particle size 8 μm) was added to a solvent (NMP) and mixed thoroughly. Using polyethylene (PE) as the base film, a first slurry is coated on both sides of the base film to form a first layer, and a second slurry is sprayed onto the first layer to obtain a release film.

[0186] On the separator, the one-sided density of the coating on the base film and the mass ratio of alumina to polyvinylidene fluoride, based on the mass of solid components, are the same as in Example 1.

[0187] Comparative Example 2 The preparation of the battery cell in Comparative Example 2 was similar to that in Example 3, except that the separator coating was a double-layer coating. The preparation of the separator in Comparative Example 2 was the same as that in Comparative Example 1.

[0188] Comparative Example 3 The preparation of the battery cell in Comparative Example 3 was similar to that in Example 3, except that fluorobenzene was not added to the electrolyte.

[0189] II. Battery Performance Testing 1) Cycle life test method: Place the battery cell at 25℃, charge it at 1C constant current to the cutoff voltage of 3.65V, charge it at constant voltage to 0.05C, let it stand for 30 minutes, and discharge it at 1C to 2.5V. This is one charge-discharge cycle.

[0190] When the absolute value of the slope of the cycle curve rises sharply, that is, when the curve drops to an inflection point, it is considered that lithium has been deposited at this point, and the cycle number of the battery cell at this time is recorded.

[0191] 2) Volumetric Energy Density Test Method: Place the battery cell at 25℃ and charge it to 3.65V with a constant current of 0.33C, then charge it to 0.05C with a constant voltage and let it stand for 30 minutes; discharge it to 2.5V with a constant current of 0.33C and record the total energy output E0 during the discharge process, in Wh. Use calipers to measure the length, width, and height of the battery cell, calculate the volume V0 of the battery cell, in L, and the volumetric energy density of the battery cell VED = E0 / V0, in Wh / L.

[0192] 3) Test method for electrode assembly liquid absorption rate: Weigh the electrode assembly to obtain W0, immerse the bottom of the electrode assembly in 30mm of electrolyte, and measure the weight W of the electrode assembly every 1 second. x With time t as the x-axis and W x The vertical axis represents the liquid absorption rate curve. The slope of this curve characterizes the liquid absorption rate of the electrode assembly, with units of g / s.

[0193] III. Analysis of Test Results for Each Embodiment and Comparative Example Batteries for each embodiment and comparative example were prepared according to the above method, and various performance parameters were measured. The results are shown in Tables 1-4 below.

[0194] Table 1

[0195] Table 2

[0196] According to Tables 1 and 2, comparing Examples 1-5 with Comparative Examples 1-3, it can be seen that the embodiments of this application provide a battery cell, including an electrolyte and an electrode assembly. The electrode assembly includes a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrode. The negative electrode includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The separator includes a base film and a composite coating disposed on at least one side of the base film. The composite coating includes inorganic particles and binder particles. The binder particles are embedded in the inorganic particles and form protrusions on the composite coating. The electrolyte includes additives. Along a first direction, the size of the negative electrode film layer is H1, where H1 is greater than or equal to 160 mm. The first direction is parallel to the direction of gravity. This battery cell balances high energy density and cycle life.

[0197] According to Table 2 above, comparing Example 3 with Comparative Examples 1-3 shows that using a separator with a composite coating and an electrolyte containing a co-solvent significantly improves the cell's liquid absorption capacity, thereby improving the cycle life of the battery cell.

[0198] Table 3

[0199] A comparison of Examples 3, 6-11, and Comparative Example 3 shows that when the mass percentage of additives in the electrolyte is 1.5%-8%, it is beneficial to improve the matching degree between the surface tension of the electrolyte and the surface energy of the separator with the composite coating, thereby further improving the cycle life of the battery cell. A comparison of Examples 3, 8-9, and Examples 6-7 and 10-11 shows that an electrolyte viscosity of 2.49 mPa·s-3.17 mPa·s can improve the wettability and interfacial stability of the electrolyte, reduce electrolyte evaporation and uneven ion migration, improve the risk of electrolyte shortage and lithium plating at the top of the battery cell, further improve cycle life while maintaining energy density.

[0200] Table 4

[0201] A comparison of Examples 3, 12-13 and Comparative Example 4 shows that increasing the height of the negative electrode film layer leads to a deterioration in cycle life. The embodiments of this application, through the above-mentioned technical solutions, can significantly improve the cycle life of high-energy-density battery cells with a negative electrode film layer height (i.e., the dimension along the first direction) of 160mm-500mm, achieving a balance between high energy density and high cycle life.

[0202] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A battery cell, characterized in that, The battery cell includes an electrolyte and an electrode assembly. The electrode assembly includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The negative electrode includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The separator includes a base film and a composite coating disposed on at least one side of the base film. The composite coating includes inorganic particles and binder particles, wherein the binder particles are embedded in the inorganic particles and form protrusions on the composite coating. The electrolyte includes additives, which include one or more of the following: difluoroethylene carbonate, fluoroethylene carbonate, fluorocarboxylic acid ester, fluorobenzene, vinyl sulfate, vinyl sulfite, and propylene sulfite; and Along the first direction, the size of the negative electrode film is H1, where H1 is greater than or equal to 160 mm, and the first direction is parallel to the direction of gravity.

2. The battery cell according to claim 1, characterized in that, Based on the mass of the electrolyte, the additive accounts for 1%-10% of the total mass.

3. The battery cell according to claim 1 or 2, characterized in that, Based on the mass of the electrolyte, the additive accounts for 1.5%-8% of the total mass.

4. The battery cell according to any one of claims 1 to 3, characterized in that, At 25°C, the viscosity of the electrolyte is 1.2 mPa·s-3.8 mPa·s.

5. The battery cell according to any one of claims 1 to 3, characterized in that, At 25°C, the viscosity of the electrolyte is 2.49 mPa·s-3.17 mPa·s.

6. The battery cell according to any one of claims 1 to 5, characterized in that, The electrolyte also includes lithium salt, and the lithium salt accounts for 6%-18% of the total mass of the electrolyte.

7. The battery cell according to any one of claims 1 to 6, characterized in that, On the composite coating, the inorganic particles have an average particle size of 0.5 μm-3 μm; and / or On the composite coating, the average particle size of the binder particles is 5μm-20μm.

8. The battery cell according to any one of claims 1 to 7, characterized in that, Based on the mass of the composite coating, the mass percentage of the binder particles is greater than or equal to 25%.

9. The battery cell according to any one of claims 1 to 8, characterized in that, On the composite coating, the average particle size ratio of the binder particles to the inorganic particles is (2-35):1; and / or The mass ratio of the binder particles to the inorganic particles is 1:(1-3).

10. The battery cell according to any one of claims 1 to 9, characterized in that, The thickness of the composite coating is 0.5μm-10μm.

11. The battery cell according to any one of claims 1 to 10, characterized in that, The areal density of the composite coating is 2.4 g / m³. 2 -16.9g / m 2 .

12. The battery cell according to any one of claims 1 to 11, characterized in that, The porosity of the isolation membrane is 30%-65%.

13. The battery cell according to any one of claims 1 to 12, characterized in that, The binder particles include polyvinylidene fluoride copolymer, sodium carboxymethyl cellulose, polystyrene-butadiene copolymer, and hydrogenated styrene. Butadiene block copolymer, hydrogenated styrene Isoprene block copolymer, ethylene Butene copolymer, polypropylene Octene thermoplastic elastomer, ethylene Octene thermoplastic elastomers and propylene One or more of the ethylene copolymers.

14. The battery cell according to any one of claims 1 to 13, characterized in that, The inorganic particles include one or more of alumina, boehmite, silicon dioxide, cerium oxide, magnesium aluminate, zirconium oxide, and titanium dioxide.

15. The battery cell according to any one of claims 1 to 14, characterized in that, The base film includes one or more of polyolefins and polyamides.

16. The battery cell according to any one of claims 1 to 15, characterized in that, The thickness of the base film is 5μm-10μm.

17. The battery cell according to any one of claims 1 to 16, characterized in that, Along the first direction, the size of the negative electrode film is H1, where H1 is 160mm-500mm.

18. The battery cell according to any one of claims 1 to 17, characterized in that, The volumetric energy density of the battery cell is 412Wh / L-450Wh / L.

19. A method for preparing a battery cell, characterized in that, include: An electrode assembly is formed by a positive electrode, a negative electrode, and a separator. The negative electrode includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The size of the negative electrode film layer is H1 along a first direction, where H1 is greater than or equal to 160 mm. The first direction is parallel to the direction of gravity. The separator includes a base film and a composite coating disposed on at least one side of the base film. The composite coating includes inorganic particles and binder particles. The binder particles are embedded in the inorganic particles and form protrusions on the composite coating. The electrode assembly is placed inside the housing, and the first liquid injection is performed, followed by standing. After standing, a second electrolyte is injected. The second electrolyte used in the second electrolyte injection includes additives, which include one or more of difluoroethylene carbonate, fluoroethylene carbonate, fluorobenzene, ethylene sulfate, ethylene sulfite, and propylene sulfite to obtain a battery cell.

20. The method according to claim 19, characterized in that, Based on the mass of the second electrolyte, the additive accounts for 3.33%-66.67% of the total mass.

21. The method according to claim 19, characterized in that, Based on the mass of the second electrolyte, the additive accounts for 5%-53.33% of the total mass.

22. The method according to any one of claims 19 to 21, characterized in that, The mass ratio of the first electrolyte to the second electrolyte used for the first injection is (70:30) to (85:15).

23. A battery device, characterized in that, The battery device includes one or more of the following: battery cells as described in any one of claims 1 to 22; battery modules, battery packs, and energy storage batteries.

24. An electrical appliance, characterized in that, The electrical device includes the battery device as described in claim 23, the battery device being used to provide electrical energy.